Crecimiento Urbano De La Ciudad De Neiva En Las Dos Primeras Décadas Del Siglo XXI - Caso De Estudio Comuna 9 (2022)
This is an investigation that arises from the study of the urban growth of the city of Neiva Huila, in the commune 9 of this city, since it was possible to evidence the lack of information on this subject and the different inconsistencies about the urban planning process of the city, thus giving a rigor to the research through the collection of information in the different primary sources found, It has also been found that some people have already tried to carry out this work since its foundation until t and have verified how difficult it is to collect information. he year 2000 It is expected to be able to have an analysis about the development and growth of commune 9 from the year 2000 to the year 2020